The Illumination of Thunderclouds by Lightning: 1. The Extent and Altitude of Optical Lightning Sources. Issue 1 (10th January 2022) - Peterson, Michael; Light, Tracy E. L.; Mach, Douglas
Abstract: Optical space‐based lightning sensors including NOAA's Geostationary Lightning Mapper (GLM) detect lightning though its transient illumination of the surrounding clouds. What space‐based optical lightning sensors measure is influenced by the physical attributes of the light source, the location of the source within the cloud scene, and the spatial variations in cloud composition. We focus on the lightning channels that serve as optical sources for GLM groups and flashes in this first part of our thundercloud illumination study. We match Lightning Mapping Array (LMA) sources with GLM groups and flashes during two thunderstorms to examine channel segments that are active during optical emission. We find that in each storm, the LMA sources matched with GLM groups are small (median: 3 km) compared to GLM pixels (nominal: 8 km), and preferentially come from high altitudes in the cloud (>8–10 km). The detection advantage for high‐altitude sources permits GLM to resolve faint optical pulses near the cloud top that might be missed from lower altitudes. However, the most energetic groups can be detected from all altitudes, and the largest groups largely originate at low altitudes. The relationship between group energy and illuminated area depends on flash development within the cloud medium, and flash development into different cloud regions can be identified by tracking GLM metrics of cloud illumination over time. Plain Language Summary: Lightning flashes are detected from space by monitoring cloud‐top brightness for rapid changes due to illumination from lightning. The amount of lightning that instruments like the Geostationary Lightning Mapper (GLM) can detect depends on how the clouds are illuminated by lightning. Small, dim flashes are difficult to detect because they only faintly illuminate the surrounding clouds. However, even bright sources below particularly thick clouds might not cause enough illumination to trigger the sensor. This study begins a comprehensive analysis of the thundercloud illumination that is measured by GLM, impacts on instrument performance, and the opportunities it presents for characterizing flashes and their environments in new and unique ways. Key Points: Geostationary Lightning Mapper (GLM) measurements of thundercloud illumination are compared with Lightning Mapping Array (LMA) measurements of flash structure and Earth Networks Global Lightning Network stroke detections The GLM detection advantage for high‐altitude sources is quantified, and shown to vary with group area and energy Group maximum separation is a better approximation of LMA flash extent than event‐based size metrics, but it is limited by GLM sensitivity